158k views
2 votes
#16 please help me solve this

#16 please help me solve this-example-1
User NLV
by
6.3k points

2 Answers

4 votes

Answer:

y=4, x=-5

Explanation:

Ⓗⓘ ⓣⓗⓔⓡⓔ

Well, we could merge the two equations together to do as shows:

4(2y-13)-3y=-32

8y-52-3y=-32

5y-52=-32

5y=20

y=4

To find x, we'd do

4x-3(4)=-32

4x-12=-32

4x=-20

x=-5

(っ◔◡◔)っ ♥ Hope this helped, have a great day! ♥

˜”*°•.˜”*°• ~Star •°*”˜.•°*”˜

User Mor Paz
by
5.0k points
0 votes

Answer:

x=-5, y=4

Explanation:

4x - 3y = -32

x = 2y -13

Use the second equation to substitute for x in the first equation

4(2y-13) -3y = -32

Distribute

8y -52-3y = -32

Combine like terms

5y -52 = -32

Add 52 to each side

5y -52+52 = -32+52

5y = 20

Divide by 5

5y/5 = 20/5

y=4

Now we need to solve for x

x = 2y-13

=2(4) -13

8-13

= -5

User Protoproto
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.